Pathogen exposure varies widely among sympatric populations of wild and domestic felids across the United States. Issue 2 (24th May 2016) - Carver, Scott; Bevins, Sarah N.; Lappin, Michael R.; Boydston, Erin E.; Lyren, Lisa M.; Alldredge, Mathew; Logan, Kenneth A.; Sweanor, Linda L.; Riley, Seth P. D.; Serieys, Laurel E. K.; Fisher, Robert N.; Vickers, T. Winston; et al.
Abstract: Understanding how landscape, host, and pathogen traits contribute to disease exposure requires systematic evaluations of pathogens within and among host species and geographic regions. The relative importance of these attributes is critical for management of wildlife and mitigating domestic animal and human disease, particularly given rapid ecological changes, such as urbanization. We screened >1000 samples from sympatric populations of puma ( P uma concolor ), bobcat ( L ynx rufus ), and domestic cat ( Felis catus ) across urban gradients in six sites, representing three regions, in North America for exposure to a representative suite of bacterial, protozoal, and viral pathogens ( Bartonella sp., Toxoplasma gondii, feline herpesvirus‐1, feline panleukopenea virus, feline calicivirus, and feline immunodeficiency virus). We evaluated prevalence within each species, and examined host trait and land cover determinants of exposure; providing an unprecedented analysis of factors relating to potential for infections in domesticated and wild felids. Prevalence differed among host species (highest for puma and lowest for domestic cat) and was greater for indirectly transmitted pathogens. Sex was inconsistently predictive of exposure to directly transmitted pathogens only, and age infrequently predictive of both direct and indirectly transmitted pathogens. Determinants of pathogen exposure were widely divergent between the wild felid species. For puma, suburban land use predicted increased exposure to Bartonella sp. in southern California, and FHV‐1 exposure increased near urban edges in Florida. This may suggest interspecific transmission with domestic cats via flea vectors (California) and direct contact (Florida) around urban boundaries. Bobcats captured near urban areas had increased exposure to T. gondii in Florida, suggesting an urban source of prey. Bobcats captured near urban areas in Colorado and Florida had higher FIV exposure, possibly suggesting increased intraspecific interactions through pile‐up of home ranges. Beyond these regional and pathogen specific relationships, proximity to the wildland–urban interface did not generally increase the probability of disease exposure in wild or domestic felids, emphasizing the importance of local ecological determinants. Indeed, pathogen exposure was often negatively associated with the wildland–urban interface for all felids. Our analyses suggest cross‐species pathogen transmission events around this interface may be infrequent, but followed by self‐sustaining propagation within the new host species.